2008
DOI: 10.1093/sleep/31.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Sleep Parameters from Actigraphy and Polysomnography in Older Women: The SOF Study

Abstract: Sleep parameters from actigraphy corresponded reasonably well to PSG in this population, with the PIM mode of actigraphy correlating highest. Those with poor sleep quality had the largest measurement error between the 2 procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
204
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 244 publications
(211 citation statements)
references
References 34 publications
5
204
2
Order By: Relevance
“…Because all actigraphy-based parameters were restricted to the early follicular phase in all female subjects, our findings do not account for potential variability in sleep patterns across the menstrual cycle (3) or investigate the effects of female sex hormones on nocturnal hemodynamic dipping. Finally, we acknowledge that while several studies have validated actigraphy-accessed sleep efficiency against the gold-standard polysomnography (1,11,26,29,34,42), some studies have found variation in the calculation of sleep efficiency between the two techniques (5,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because all actigraphy-based parameters were restricted to the early follicular phase in all female subjects, our findings do not account for potential variability in sleep patterns across the menstrual cycle (3) or investigate the effects of female sex hormones on nocturnal hemodynamic dipping. Finally, we acknowledge that while several studies have validated actigraphy-accessed sleep efficiency against the gold-standard polysomnography (1,11,26,29,34,42), some studies have found variation in the calculation of sleep efficiency between the two techniques (5,40).…”
Section: Discussionmentioning
confidence: 99%
“…Objective measurements of sleep time, sleep efficiency, sleep onset latency (SOL), and wake after sleep onset (WASO) were acquired from the actigraph watch. Actigraphy measurements of these sleep parameters have been validated against the gold standard polysomnography (1,5,11,26,29,34,40,42). Actigraphy sleep measurements were averaged over the 7 nights, with an average of 6 Ϯ 1 nights per subject.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the analyses, the sleep parameter predictor variables other than TST were expressed as dichotomous variables based on published cutpoints for sleep disturbances, [23][24][25][26][27][28][29][30] many of which define moderate to severe impairment: SE < 70% (reduced SE) versus ≥ 70%; SL ≥ 1 hour (prolonged SL) versus < 1 hour; WASO ≥ 1.5 hour (greater WASO) versus < 1.5 hour; PSQI > 8 (poorer subjective sleep quality) versus ≤ 8; and ESS > 10 (excessive daytime sleepiness) versus ≤ 10). Based on the possibility that there is a U-shaped association between TST and health-related outcomes, TST was expressed as a three-level predictor: shorter sleep duration (<5 hours/night); normal sleep duration (≥5 and ≤8 hours/night, referent group); and longer sleep duration (>8 hours/night).…”
Section: Discussionmentioning
confidence: 99%
“…Actigraphy becomes less reliable for differentiating sleep from wake in patients with more disturbed sleep (Ancoli-Israel et al, 2003) and this may account for the lack of association between these measures. In a study of older women, Blackwell et al (2008) reported an overestimation of SE and underestimation of WASO, problems that were greatest in participants with fragmented sleep. Therefore sleep parameters from actigraphy should be interpreted cautiously.…”
mentioning
confidence: 96%